The Tiwanaku Camelid Sacrificer: Origins and transformations of animal iconography in the context of Middle Horizon (A.D. 400–1100) state expansion. (2nd January 2019) - Baitzel, Sarah I.; Trigo Rodríguez, David E.
Abstract : Prehispanic Andean iconography communicated ideology and structures of power. On the coast, iconography depicting violence and fertility legitimized elite power. In Tiwanaku (A.D. 400–1100), such iconography is considered to have been absent. We re-examine the theme of the Sacrificer in Tiwanaku iconography that originated during the Formative period in the south-central Andes. This figure, which we term Tiwanaku Camelid Sacrificer (TCS), takes on a new appearance: a human-camelid body carrying a a trophy head or axe. The TCS imagery is often depicted on portable prestige objects, many of them found in the Tiwanaku hinterlands that relied economically and socially on caravans. We propose that the TCS represents aspects of Tiwanaku ritual and ontology, by which camelids and humans shared acts, essence, and form. The states of being ( camay ) and becoming ( tucoy ) embodied by the TCS testify to the unique positions of power camelids held over life in Tiwanaku's agropastoralist society.